Analisis Semiotika Promosi Vape di Akun Instagram @lostvape.indonesia Sebagai Representasi Gaya Hidup Gen Z - Kurdiyanto, Danik; S. Khayan, Fika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze how Generation Z's lifestyle is represented and how digital marketing strategies are used in promoting vape products on the Instagram account @lostvape.indonesia through Roland Barthes' semiotic approach. Using a qualitative descriptive method, the study observes visual and verbal signs in the vape content and explains their denotative, connotative, and myth meanings. The findings show that vape promotion does more than sell products; it also builds images of freedom, creativity, and social identity that attract Generation Z. The semiotic strategy helps to understand how the signs in digital ads create meaning and influence the audience’s perception. This research contributes to the study of digital marketing communication and semiotic analysis of social media advertising while providing practical insights for designing effective and ethical promotional campaigns.